Comparative analysis of Generation Z’s digital history literacy in history education majors on Java Island: A study of history digital literacy - Kumalasari, Dyah; Purwanta, Hieronymus; Aw, Suranto (Journal of Education and e-Learning Research, 2024)
The purpose of this study is to determine the level of digital literacy related to history among students at Universitas Pendidikan Indonesia (UPI) and the State University of Malang (UM). The recent decline in historical literacy among Indonesians has piqued historians’ interest. In this context, the gap between technological potential and literacy problems may be advantageous for initiatives to enhance Indonesian young historical literacy. This research uses a quantitative-descriptive approach. The respondents were first-year and second-year history students at UPI and UM. The data collection technique used was a historical literacy test that has Higher Order Thinking Skills (HOTS) levels 1-4. This study used descriptive data analysis and an independent sample t-test. The results of this study show that students from both universities have a low level of historical literacy, both in first-year and second-year students. This condition is a signal for teachers to start improving. Gadget technology is suggested as a solution to the problem because these students belong to Generation Z (a generation that is very aware of current events and technological advancements). The methodology of Scholarship of Teaching and Learning (SOTL) was selected because its principles are appropriate for fostering digital historical literacy. It is student-focused, context-based, collaborative, methodical and well-developed in the community.